2014
DOI: 10.3109/10641955.2013.858744
|View full text |Cite
|
Sign up to set email alerts
|

An imbalance in the production of proinflammatory and anti-inflammatory cytokines is observed in whole blood cultures of preeclamptic women in comparison with healthy pregnant women

Abstract: Preeclamptic women showed an imbalance in the production of pro and anti-inflammatory cytokines in comparison with normotensive women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…IL‐1β level was similar in mild preeclampsia and healthy pregnancies, which is in line with our findings. The role of IL‐6 in placental invasiveness during implantation has been described previously, but results regarding IL‐6 levels in preeclampsia patients are rather controversial . Recent studies have not observed differences in IL‐6 levels between preeclampsia and uncomplicated pregnancies, which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
“…IL‐1β level was similar in mild preeclampsia and healthy pregnancies, which is in line with our findings. The role of IL‐6 in placental invasiveness during implantation has been described previously, but results regarding IL‐6 levels in preeclampsia patients are rather controversial . Recent studies have not observed differences in IL‐6 levels between preeclampsia and uncomplicated pregnancies, which is in agreement with our results.…”
Section: Discussionsupporting
confidence: 92%
“…27,[107][108][109] Moreover, a high level of proinflammatory cytokine (IL-1b and IL-6) profile can be demonstrated in preeclampsia. 27,110 DNA oxidation as measured by the expression of 8-OHdG in preeclamptic placenta is higher than in the healthy placentas. 27 Placental senescence in spontaneous preterm labor/birth.…”
Section: Perturbation Of Mitochondrial Homeostasismentioning
confidence: 92%
“…The association of both inflammatory processes and oxidative stress, and their possible role in cellular pathology was reviewed elsewhere . It was also reported that imbalance between anti‐ and pro‐inflammatory cytokines is a potential cause of PE . Unusual increase of pro‐inflammatory cytokines is also reported to be a trigger of maternal endothelial cell abnormality in PE .…”
Section: Introductionmentioning
confidence: 99%
“…12 It was also reported that imbalance between anti-and pro-inflammatory cytokines is a potential cause of PE. 13 Unusual increase of pro-inflammatory cytokines is also reported to be a trigger of maternal endothelial cell abnormality in PE. 14 Pro-inflammatory cytokine levels, such as tumor necrosis factor-α (TNF-α) and interleukin (IL)-6, have also been reported to be changed during PE.…”
Section: Introductionmentioning
confidence: 99%